2015
DOI: 10.1038/ncomms7025
|View full text |Cite
|
Sign up to set email alerts
|

Activating mutations of STAT5B and STAT3 in lymphomas derived from γδ-T or NK cells

Abstract: Lymphomas arising from NK or gd-T cells are very aggressive diseases and little is known regarding their pathogenesis. Here we report frequent activating mutations of STAT3 and STAT5B in NK/T-cell lymphomas (n ¼ 51), gd-T-cell lymphomas (n ¼ 43) and their cell lines (n ¼ 9) through next generation and/or Sanger sequencing. STAT5B N642H is particularly frequent in all forms of gd-T-cell lymphomas. STAT3 and STAT5B mutations are associated with increased phosphorylated protein and a growth advantage to transduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
264
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(298 citation statements)
references
References 44 publications
12
264
1
Order By: Relevance
“…STATs display a tight regulation of the expression of genes whose protein products regulate critical processes such as proliferation, survival, differentiation, senescence, metabolism, angiogenesis, and invasion [123]. Constitutive activation of STAT3/5 is commonly found in MPN and PTCL [20,124]. Consistent with the prediction that oncogenic transcription factors are triggered downstream of many activated drivers, STATs are activated much more commonly than any single genetic driver mutation [125].…”
Section: Current Therapies and Novel Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…STATs display a tight regulation of the expression of genes whose protein products regulate critical processes such as proliferation, survival, differentiation, senescence, metabolism, angiogenesis, and invasion [123]. Constitutive activation of STAT3/5 is commonly found in MPN and PTCL [20,124]. Consistent with the prediction that oncogenic transcription factors are triggered downstream of many activated drivers, STATs are activated much more commonly than any single genetic driver mutation [125].…”
Section: Current Therapies and Novel Approachesmentioning
confidence: 99%
“…Importantly, ALK − ALCL is associated with STAT3 activation [64] and recurrent, somatic activating mutations in the closely related STAT5B gene were reported. The STAT5B N642H mutation occurs with the highest frequency in PTCL, whereby most mutations cluster in the SH 2 and C-terminal transactivation domain [70,75,7882]. A recent study found that ~70% of T-PLL patients carry JAK-STAT hyperactivating mutations [70].…”
Section: Targets In Ptcl and Driver Mutationsmentioning
confidence: 99%
“…It is also important for lymphoid cell development ( 9 ): STAT5 is constitutively active in a plethora of lymphoid malignancies ( 10 ). Recent studies have described somatic Stat5b mutations as active drivers of lymphoid malignancies ( 11,12 ), and considerable efforts are under way to develop STAT5 inhibitors. Such inhibitors will not only target malignant hematopoietic cells but will also have severe consequences for immune functions that depend on the activation of STAT5 by cytokines.…”
Section: Stat5 Is a Key Regulator In Nk Cells And Acts As A Molecularmentioning
confidence: 99%
“…1 T-LGL leukemia have also been seen in various T-cell neoplasms, including gd hepatosplenic T-cell lymphoma, 13 T-cell acute lymphoblastic leukemia, 14,15 T-cell prolymphocytic leukemia, 16 type II enteropathy-associated T-cell lymphoma, 17 and extranodal NK/T-cell lymphoma, 18 suggesting that these are shared with other T-cell malignancies. The analyses of STAT5 target genes with chromatin immunoprecipitation sequencing have shown that STAT5B is a key factor in T-cell development, binding to molecules such as DOCK8, SNX9, FOXP3, and IL2RA.…”
mentioning
confidence: 99%